A Regional, Strategic Growth-Management Approach to Urban and Peri-Urban Development in South East Queensland, Australia - Bhishna Nanda Bajracharya; Peter Hastings (The Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
The approach and efficacy of South East Queensland's (Australia) regional planning strategy to manage urban and peri-urban growth is described and discussed from document analysis. Framed within the urban containment paradigm, the South East Queensland Regional Plan 2017 establishes specific principles and statutory planning controls to direct the spatial distribution of growth while attempting to preserve natural, cultural and productive landscapes and overall liveability. Identification of desired regional growth patterns, coordinated governance, economic and infrastructure development, and plan monitoring are key attributes of a framework that has generally resulted in acceptable regional outcomes. Nevertheless, a number of challenges remain for containing urban growth and maintaining regional resilience and sustainability amidst continuing growth pressures. This paper highlights three contemporary issues of interest: greater recognition and delineation of peri-urban areas, integration of regional planning and disaster management, and growth management of peri-urban master planned communities. The need for ongoing, independent plan evaluation is also identified.Keywords. Urban development, regional planning, peri-urban development, growth management, governance, South East Queensland.Abstrak. Pendekatan dan keberhasilan perencanaan stretegis wilayah South East Queensland (Australia) dalam mengelola pertumbuhan perkotaan dan peri-urban dijelaskan dan didiskusikan dari dokumen analisis. Dibingkai dalam paradigma pembatasan perkotaan (urban containment), South East Queensland Regional Plan 2017 menetapkan prinsip-prinsip spesifik dan peraturan pengendalian perencanaan untuk mengarahkan distribusi spasial pertumbuhan diiringi dengan upaya pelestarian lingkungan, lahan budidaya dan lahan produktif, serta tingkat kualitas hidup secara keseluruhan. Identifikasi pola pertumbuhan regional yang diinginkan, tata kelola pemerintahan yang terkoordinasi, pembangunan ekonomi dan infrastruktur, dan pemantauan rencana merupakan faktor kunci untuk menghasilkan dampak wilayah yang dikehendaki. Namun demikian, masih terdapat sejumlah tantangan untuk melakukan pembatasan pertumbuhan kota dan mempertahankan ketahanan dan keberlanjutan wilayah masih tampak di tengah tekanan pertumbuhan yang terus berlanjut. Makalah ini menyoroti tiga isu kontemporer, yaitu pengakuan yang lebih besar dan penggambaran wilayah peri-urban, integrasi perencanaan wilayah dan manajemen bencana, dan manajemen pertumbuhan komunitas perencanaan induk peri-urban. Makalah ini juga mengidentifikasi kebutuhan untuk evaluasi rencana yang independen dan berkelanjutan.Kata Kunci. Pembangunan perkotaan, perencanaan regional, pengembangan peri-urban, manajemen pertumbuhan, pemerintahan, Queensland Tenggara.